Prevalence and Costs of Complementary/Alternative Medicine among Traumatic Patients in Iran: A Nationwide Population-based Study - Mohammad Hosein KALANTAR MOTAMEDI; Abolfazl ABOUIE; Nima HAFEZI-NEJAD; Soheil SAADAT; Afarin RAHIMI-MOVAGHAR; Abbas MOTEVALIAN; Masoumeh AMIN-ESMAEILI; Vandad SHARIFI; Ahmad HAJEBI; Ali EBRAHIMI; Vafa RAHIMI-MOVAGHAR (Tehran University of Medical Sciences, 2018)
Background: This study was aimed to determine the prevalence, predictors and cost of CAM practitioner use among traumatic patients in Iran. Methods: This cross-sectional household survey of a nationally representative sample of Iranians 15 to 64 yr old was conducted in 2011, using a three-stage cluster sampling. Short Form Injury Questionnaire 7 (SFIQ7) was utilized through face-to-face interviews and data on demographics, history of injuries, mechanism, site and type of injury, type and place of the treatment were attained. Via telephone calls, service use and costs of treatment were also collected. Results: The prevalence of CAM practitioner use in injured people and victims seeking medical care was 0.7% and 4.1%, respectively in 3-month interval in 2011. There were no significant sociodemographic differences between victims who seek unconventional settings and those who seek conventional treatment. The most common injury description treated by CAM providers was as follows: fracture (type of injury), upper limb (site of injury), fall (mechanism of injury) and cast, splint, and physiotherapy (type of treatment). The average medical cost of CAM practitioner was US$14.7 while this amount in the conventional setting was US$195.5. Conclusion: Use of CAM is not very common among injured people in Iran. However, due to lack of formal training, CAM usage has possible side effects.